2006
DOI: 10.1021/cb600303y
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Reverse Transcriptase Structure with RNase H Inhibitor Dihydroxy Benzoyl Naphthyl Hydrazone Bound at a Novel Site

Abstract: The rapid emergence of drug-resistant variants of human immunodeficiency virus, type 1 (HIV-1), has limited the efficacy of anti-acquired immune deficiency syndrome (AIDS) treatments, and new lead compounds that target novel binding sites are needed. We have determined the 3.15 Å resolution crystal structure of HIV-1 reverse transcriptase (RT) complexed with dihydroxy benzoyl naphthyl hydrazone (DHBNH), an HIV-1 RT RNase H (RNH) inhibitor (RNHI). DHBNH is effective against a variety of drug-resistant HIV-1 RT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
176
0
2

Year Published

2008
2008
2014
2014

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(185 citation statements)
references
References 49 publications
(96 reference statements)
7
176
0
2
Order By: Relevance
“…Crystal structures of HIV-1 RT RNase H with a bound active site inhibitor confirmed that these compounds are anchored at the RNase H active site and interact with the bound divalent metal ions (22)(23)(24)(25). Allosteric RNase H inhibitors can bind in the vicinity of the polymerase active site as shown for N-acyl hydrazones (26,27), or in the vicinity of the p51 thumb subdomain as shown for vinylogous ureas (28,29).…”
mentioning
confidence: 86%
“…Crystal structures of HIV-1 RT RNase H with a bound active site inhibitor confirmed that these compounds are anchored at the RNase H active site and interact with the bound divalent metal ions (22)(23)(24)(25). Allosteric RNase H inhibitors can bind in the vicinity of the polymerase active site as shown for N-acyl hydrazones (26,27), or in the vicinity of the p51 thumb subdomain as shown for vinylogous ureas (28,29).…”
mentioning
confidence: 86%
“…Since the RNase H function is essential for viral replication (5), it has been explored as a drug target, and a number of RNase H inhibitors (RHIs) have been reported (6)(7)(8). RHIs can be classified based on their binding sites, i.e., (i) RHIs that coordinate the two Mg 2ϩ catalytic cofactors at the RNase H active site, such as N-hydroxyimides (9), hydroxytropolones (10), hydroxypyrimidines (11), naphthyridinones (12), nitrofuran-2-carboxylic acid carbamoylmethyl esters (13), hydroxyquinolinones (14), and thiocarbamates and triazoles (15), or (ii) allosteric RHIs, such as vinylogous ureas (16), thienopyrimidinones (17), hydrazones (18), anthraquinones (19), isatines (20,21), and propenones (22).…”
mentioning
confidence: 99%
“…During the last 10 years, several classes of HIV-1 RHIs have been identified (12)(13)(14)(15). The design of potent RHIs has proven difficult due to the open morphology of the RNase H active site (16) and the limited number of available RNase H crystal structures in complex with inhibitors (17)(18)(19)(20)(21). In addition, given the fact that under nuclear magnetic resonance (NMR) conditions, the free HIV-1 RNase H domain is stable only in the presence of 20 to 80 mM MgCl 2 , it is difficult to perform binding studies with inhibitors that interact with magnesium ions (22)(23)(24).…”
mentioning
confidence: 99%